التذوق البلاغي للنظم القرآني وأهميته في تعليم البلاغة للناطقين بغير العربية / Rhetorical Taste of Qur'anic Systems and its Importance in Teaching Rhetoric toward Non-Arabic Speakers - A-eshah Waemamah; Siti Salwa Mohd Noor; Abdul wahid Salleh (Diwan : Jurnal Bahasa dan Sastra Arab, 2022)
هدفت الدراسة إلى بيان التذوق البلاغي للنظم القرآني وأهميته في تعليم البلاغة للناطقين بغير العربية. وتم استخدام المنهج الوصفي التحليلي من خلال المراجع ذات الصلة، للكشف عن مفهوم التذوق البلاغي للنظم القرآني وأهميته في حقل تعليم البلاغة للناطقين بغير العربية . وأظهرت الدراسة إلى أن التذوق البلاغي للنظم القرآني يعتبر هدفا يجب تحقيقه في تعليم البلاغة للناطقين بغير العربية لإدراك وجوه الإعجاز البلاغي للقرآن الكريم. ولذلك توصي الدراسة بأهمية الأخذ بالاعتبار التذوق البلاغي ولا سيما للنظم القرآني في تعليم البلاغة للناطقين بغير العربية. الكلمات المفتاحية : التذوق البلاغي؛ تعليم البلاغة؛ الناطقين بغير العربية. Abstract The study sought to uncover the rhetorical appreciation of the Quranic systems, as well as its significance in teaching rhetoric to non-Arabic speakers.. The analytical-descriptive approach was used in the relevant literature to reveal the concept of rhetorical appreciation for Quranic systems and its importance in teaching rhetoric to non-Arabic speakers. The study showed that the rhetorical appreciation of the Quranic systems is a goal that must be achieved in teaching rhetoric to non-Arabic speakers to realize the aspects of the rhetorical miracle of the Holy Qur’an. The study recommends the importance of taking into account rhetorical appreciation, especially the Quranic systems, in teaching rhetoric to non-Arabic speakers.